Integration of The Principle of Restorative Justice In Law Enforcement of Tax Crimes To Achieve Legal Certainty In Indonesia - Soesilo Soesilo; Fauzie Yusuf Hasibuan; Maryano Maryano (Asian Journal of Social and Humanities, 2024)
This research analyses the implementation of judges' decisions on law enforcement of taxation crimes in Indonesia and identifies ideal criminal law policies to achieve legal certainty. The method used is normative juridical with analytical descriptive approach, which is supported by the theory of judicial power, theory of legal certainty, and theory of law enforcement. The results show that the ultimum remedium principle has not been fully applied consistently, with some serious tax offences going directly to the criminal realm even though administrative mechanisms are still possible. Conversely, some other offences are resolved administratively, even though the criminal elements have been fulfilled. This inconsistency suggests the need for uniform technical guidelines to reduce differences in legal interpretation. This research is an integration of restorative justice principles in Indonesian tax law, which allows offenders to settle tax liabilities along with penalties before being subject to criminal sanctions. This approach balances the recovery of state losses and the deterrent effect for offenders, while supporting sustainable taxpayer compliance. This research recommends the preparation of pretrial guidelines and harmonization of regulations to improve legal certainty in tax cases in Indonesia.